Morphological and histological changes in the human radial artery in multifocal atherosclerosis - K. M. Mikhailov; D. V. Kuznetsov; I. F. Nefedova; E. N. Nikolaeva; A. A. Gevorgyan; V. V. Novokshenov; A. V. Kryukov; S. M. Khokhlunov (Вестник хирургии имени И.И. Грекова, 2022)
The OBJECTIVE of our study was to research changes in the radial artery in patients with multifocal atherosclerosis and associated risk factors.METHODS AND MATERIALS. The object of the study was fragments of the human radial artery extracted during coronary bypass surgery. Patients were divided into 2 main groups: group 1 – patients who, in addition to coronary artery disease, had multifocal atherosclerosis. Group 2 – patients who did not have concomitant lesions of the main arteries. The groups did not differ statistically by gender and age. Morphological and histological studies of the preparations of the radial artery wall were carried out.RESULTS. The analysis revealed such changes as: edema of one layer of the artery or all three, proliferation of the subendothelial layer of the endarterium, intimal fibrosis, overlap of the artery lumen with a massive accumulation of agglutinated red blood cells, as well as occlusions of the radial artery.CONCLUSION. Statistical analysis of the results revealed that the combination of the above-mentioned histological factors is an early sign of atherosclerotic lesions of the radial artery wall, as well as confirmed that changes in the radial artery wall are not related to the initial wall thickness and diameter.